FEATURES OF APPLICATION OF SOFTWARE IN THE PROCESS OF TEACHING ART DISCIPLINES - Сопіна Л.Г. L.G. (SWorldJournal, 2022)
The publication raises the issue of using the capabilities of software in the teaching of art disciplines in the specialty “Secondary Education. Musical art”.The work contains a brief overview of the main areas of use of information and communication tech